Steinmann Pins and Polymethylmethacrylate Repair of Fourth Lumbar Vertebral Fracture and Dorsocranial Luxation in PuppySteinmann Pins and Polymethylmethacrylate Repair of Fourth Lumbar Vertebral Fracture and Dorsocranial Luxation in Puppy - da Silva Sobrinho, Fernando Bezerra; dos Santos, Ivan Felismino Charas; Brandão, Claudia Valéria Seullner; Rahal, Sheila Canevese; Lobo, César Passareli Cândido; Machado, Vânia Maria Vasconcelos; Moraes, Gabriel Godoi; Da Silva, Táina Aparecida Pereira (Acta Scientiae Veterinariae, 2020)
Background: Acute spinal traumas can lead to irreversible damage associated with vascular and inflammatory changes in neural tissue. Since spine and spinal cord traumas have an unfavorable prognosis in small animals, and reports of the use of Steinmann pins and polymethylmethacrylate repair of lumbar vertebra fracture-luxation in puppies are rare in the literature, the present paper aimed to report the surgical treatment of transversal fracture through the body of the fourth lumbar vertebra, with dorsocranial displacement of the caudal fragment by using Steinmann pins and polymethylmethacrylate in a 7-month-old Labrador Retriever male dog. Case: A 7-month-old intact male Labrador Retriever dog, weighing 24.0 kg was attended at School Veterinary Hospital with a history of hit by car and paraplegia of the hind limbs. On neurological examination was observed no proprioception and no deep pain sensitivity on the both pelvic limbs. The lumbar spinal palpation showed intense pain, and the motor function and patellar reflexes were reduced. The values of haematological and biochemical analysis remained within the reference values for the species. Radiographs revealed a transversal fracture through the body of the fourth lumbar vertebra, with dorsocranial displacement of the caudal fragment, and was decided to perform a surgical treatment by open reduction and internal fixation of the fracture. The dog was positioned in ventral recumbency for surgery, and a dorsal midline incision was made from the second lumbar vertebra to the sixth lumbar vertebra. Two crossed 1.5 mm Kirschner wires were placed through the caudal articular facets of the fourth lumbar vertebra to provide initial stability. Two 2.0 mm Steinmann pins were placed at 60° angle of the bodies of the second and fifth lumbar vertebrae, and third and fourth lumbar vertebrae. This procedure was repeated on the other side of the vertebral bodies. Sixty grams of polymethylmethacrylate bone cement was applied and the fixation was checked for stability. Muscular, subcutaneous tissue and skin was closed routinely. The dog was paraplegic without any pain and used a wheelchair to assist in locomotion, although it still had urinary and faecal incontinence; no tail control; and the implants were not removed. Discussion: Lumbar vertebral injuries, as in the present case frequently, occur secondary to severe trauma (e.g. hit by car) and seem to have a characteristic fracture pattern. The patient became paraplegic due to spinal cord injury and failure of sensitivity and elimination of urine and feces which can be associated with progressive destruction of neuronal tissue due to secondary vascular and inflammatory events. The radiographic exam was used to confirm the spinal injury and determine whether by conservative or surgical treatment. The treatment choice is related to the number of fractured compartments, and the presence or not of compression. Fractures in two or more compartments are indicative of surgical treatment, similar as the present case. Use of Steinmann pins was to make a rigid fixing system compared with block plates used for the same function. Use of polymethylmethacrylate may also become a complication due to the infection, for this reason was prescribed an antibiotic for 15 days. This procedure proved to be effective since the dog showed no signs of infection. According to the characteristics of the present case report, the use of Steinmann pins and polymethylmethacrylate for repair of transversal fracture through the body of the fourth lumbar vertebra, with dorsocranial displacement of the caudal fragment provided an effective and practical means of stabilisation, promoting decompression, and thus, improving the patient’s quality of life.